THE HERITABILITY ESTIMATES OF LINEAR TYPE TRAITS IN SAHIWAL COWS - M. A. Khan; M.S. Khan (Journal of Animal and Plant Sciences, 2016)
The present study was designed to get estimates of heritability for linear type traits of Sahiwal cattle. There were 790 observations on linear type traits of 310 cows scaled and scored at three stages of lactation. The cows were progeny of 53 sires with parity first to fifth. An animal model was fitted for estimation of variance component. Variance parameters were estimated using residual or restricted maximum likelihood (REML) procedures. The univariate animal model heritability estimates and standard errors were for stature 0.81±0.02, chest width 0.63±0.03, body depth 0.67±0.03, angularity 0.51±0.04, rump angle 0.52±0.04, rump width 0.78±0.02, rear legs set 0.72±0.02, rear legs rear view 0.76±0.02, foot angle 0.74±0.02, fore udder attachment 0.79±0.02, rear udder height 0.53±0.04, central ligament 0.77±0.02, udder depth 0.65±0.03, teat placement rear view 0.83±0.02, teat length (fore) 0.88±0.01, rear udder width 0.51±0.04, thurl width 0.62±0.03, navel length 0.93±0.01, dewlap width 0.73±0.02, dewlap surface area 0.59±0.03 and dewlap visual score 0.82±0.02. The heritability estimates obtained for linear type traits were in high range. These should be considered preliminary because of smaller data set. The estimates however indicated that a rapid change in desired direction is possible for most of the traits.
Keywords: Sahiwal cattle; type traits; linear score; heritability estimates